Validating Satellite‐Derived Vegetation Phenology Products: Second International Workshop on the Validation of Satellite‐Based Land Surface Phenology Products; Milwaukee, Wisconsin, 14 September 2012. (26th March 2013) - Dash, Jadu; Jones, Matthew; Nightingale, Joanne
Abstract : The phenology of terrestrial vegetation, i.e., the timing of events such as bud burst, leaf development, and senescence, plays an important role in the global climate system, biogeochemical cycles, and energy budget. Satellite‐derived vegetation indices have long been used as proxies for representing the status of terrestrial vegetation, and hence, the time series of these data sets were used to derive key land surface phenological variables such as the start and end of the growing season. Despite an increase in effort toward characterization of vegetation phenology from satellite data, its validation with ground measurements is still challenging because of mismatches in both spatial and temporal scales between the two types of measurements, distribution of ground measurements, and spatial heterogeneity of vegetation types in a satellite sensor pixel.